Detection of ubiquitin-proteasome enzymatic activities in cells: Application of activity-based probes to inhibitor development - Kramer, H; Nicholson, B; Kessler, B; Altun, M (2012)
Background: Synthetic probes that mimic natural substrates can enable the detection of enzymatic activities in a cellular environment. One area where such activity-based probes have been applied is the ubiquitin-proteasome pathway, which is emerging as an important therapeutic target. A family of reagents has been developed that specifically label deubiquitylating enzymes (DUBs) and facilitate characterization of their inhibitors. Scope of review: Here we focus on the application of probes for intracellular DUBs, a group of specific proteases involved in the ubiquitin proteasome system. In particular, the functional characterization of the active subunits of this family of proteases that specifically recognize ubiquitin and ubiquitin-like proteins will be discussed. In addition we present the potential and design of activity-based probes targeting kinases and phosphatases to study phosphorylation. Major conclusions: Synthetic molecular probes have increased our understanding of the functional role of DUBs in living cells. In addition to the detection of enzymatic activities of known members, activity-based probes have contributed to a number of functional assignments of previously uncharacterized enzymes. This method enables cellular validation of the specificity of small molecule DUB inhibitors. General significance: Molecular probes combined with mass spectrometry-based proteomics and cellular assays represent a powerful approach for discovery and functional validation, a concept that can be expanded to other enzyme classes. This addresses a need for more informative cell-based assays that are required to accelerate the drug development process. This article is part of a Special Issue entitled: Ubiquitin Drug Discovery and Diagnostics. © 2012 Elsevier B.V.